2013
DOI: 10.3758/s13423-013-0494-0
|View full text |Cite
|
Sign up to set email alerts
|

Seeking the boundary of boundary extension

Abstract: Boundary extension (BE) is a remarkably consistent visual memory error in which participants remember seeing a more wide-angle image of a scene than was actually viewed (Intraub & Richardson, Journal of Experimental Psychology: Learning, Memory, and Cognition 15:179-187, 1989). Multiple stimulus factors are thought to contribute to the occurrence of BE, including object recognition, conceptual knowledge of scenes, and amodal perception at the view boundaries (Intraub, Wiley Interdisciplinary Reviews: Cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 21 publications
6
35
1
Order By: Relevance
“…Within the multisource model of spatial representation, amodal completion is included as a contributor to BE (Intraub, 2010(Intraub, , 2012, and the strength of this contribution has been recently highlighted using very abstract scenes (Hale, Brown, McDunn, & Siddiqui, 2015;McDunn, Siddiqui, & Brown, 2014). In fact, an occluded edge is not enough to highlight the limited scope of a view (McDunn et al 2014), and Hale et al had to present extremal edges to stop participants from extending the boundaries of scenes of random abstract polygons on a field of random dots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the multisource model of spatial representation, amodal completion is included as a contributor to BE (Intraub, 2010(Intraub, , 2012, and the strength of this contribution has been recently highlighted using very abstract scenes (Hale, Brown, McDunn, & Siddiqui, 2015;McDunn, Siddiqui, & Brown, 2014). In fact, an occluded edge is not enough to highlight the limited scope of a view (McDunn et al 2014), and Hale et al had to present extremal edges to stop participants from extending the boundaries of scenes of random abstract polygons on a field of random dots.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an occluded edge is not enough to highlight the limited scope of a view (McDunn et al 2014), and Hale et al had to present extremal edges to stop participants from extending the boundaries of scenes of random abstract polygons on a field of random dots. Even with very abstract scenes-indeed, scenes with only surfaces and no objects-participants misremembered information from amodal completion as to what had been seen, showing source confusion, in support of BE as a source memory error (Hale et al 2015;McDunn et al 2014). The range of scenes across which BE is observed is quite broad, from the abstract shapes of Hale et al and McDunn et al to the rich world pictures of cities and markets in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Given the frequent interruptions of the visual input by blinks and saccades, BE may be functional in facilitating and speeding up the integration process of successive sensory input, leading to a more continuous perceptual experience of the visual surroundings. While early findings from scene memory tasks have demonstrated that BE was limited to scene memory and did not occur when objects were presented on blank backgrounds (Gottesman & Intraub, 2002;Intraub, Gottesman, & Bills, 1998), more recent research showed that BE was similarly elicited for basic objects on blank backgrounds (Konkle & Olivia, 2007) and for abstract stimuli on blank backgrounds -manipulations that eliminated context and schematic information from images (McDunn, Siddiqui, & Brown, 2014). Given these discrepant findings, in this study we investigated the necessity of object and context related conceptual information on BE.…”
mentioning
confidence: 91%
“…Thus, the explanation offered by Konkle and Oliva did not necessitate the presence of a contextual background for BE. More critically, a recent study by McDunn et al (2014) demonstrated that BE occurred even in abstract scenes consisting of irregular polygons in which semantic context and scene schema were eliminated. There were four conditions.…”
mentioning
confidence: 99%
“…Indeed, BE phenomenon was observed for a variety scene contents, including scenes with single or multiple objects, scenes with cropped and noncropped objects, and even abstract representations (Intraub & Bodamer, 1993;Intraub & Richardson, 1989;McDunn et al, 2014). However, the majority of studies did not focus on examination of BE in nonscenes.…”
Section: Introductionmentioning
confidence: 99%